Validation of the radiobiology toolkit TOPAS-nBio in simple DNA geometries. (January 2017) - McNamara, Aimee; Geng, Changran; Turner, Robert; Mendez, Jose Ramos; Perl, Joseph; Held, Kathryn; Faddegon, Bruce; Paganetti, Harald; Schuemann, Jan
Highlights: Validation study of the Monte Carlo simulation Toolkit, TOPAS-nBio, for radiobiology studies. We compare TOPAS-nBio simulations in simple DNA geometries to previously published studies. We find TOPAS-nBio predicts very similar trends of strand break yields to both comparison studies. Abstract: Computational simulations offer a powerful tool for quantitatively investigating radiation interactions with biological tissue and can help bridge the gap between physics, chemistry and biology. The TOPAS collaboration is tackling this challenge by extending the current Monte Carlo tool to allow for sub-cellular in silico simulations in a new extension, TOPAS-nBio. TOPAS wraps and extends the Geant4 Monte Carlo simulation toolkit and the new extension allows the modeling of particles down to vibrational energies ( ∼ 2 eV) within realistic biological geometries. Here we present a validation of biological geometries available in TOPAS-nBio, by comparing our results to two previously published studies. We compare the prediction of strand breaks in a simple linear DNA strand from TOPAS-nBio to a published Monte Carlo track structure simulation study. While TOPAS-nBio confirms the trend in strand break generation, it predicts a higher frequency of events below an energy of 17.5 eV compared to the alternative Monte Carlo track structure study. This is due to differences in the physics models used by each code. We also compare the experimental measurement of strand breaks from incident protons in DNA plasmids to TOPAS-nBio simulations. Our results show good agreement of single and double strand breaks predicting a similar increase in the strand break yield with increasing LET.